Interactive 3D shapes educational game for dyslexia children - Kee, Wen Sia (2014)
Dyslexia children are under the special category during their study. In fact, they are smart as normal children, but they cannot enjoy their learning process as them because of Dyslexia disorder. Therefore, this project is discussed about Interactive 3D Education Game, which is specially developed for Dyslexia children in order to provide them an adaptive and interactive education environment as well as allow them better understanding about shape's name and its properties. This educational game is divided into two main parts which are learning session and final challenge session. This method can help them understand their capabilities well. The main objective to develop this adaptive and interactive 3D education game is allowed Dyslexic children can be easy adapted into the learning environment. According to testing, this educational game is very effective to help Dyslexia children to learn 3D shape's name and its properties. They are attached to the learning environment while playing. Waterfall model approach ADDlE Model is used as a guideline to develop this educational game, which started with analysis phase, design phase, development phase, implementation phase and evaluation phase.